Зниження витрат виробництва електричних машин і апаратів при використанні аутсорсинга бізнес-процесів - Александрова, Вікторія Олександрівна (НТУ "ХПІ", 2016)
В статті розглядається актуальна проблема підприємств електротехнічної промисловості по зниженню витрат виробництва. В час економічної скрути підприємствам доцільно використовувати для зниження своїх виробничих витрат найменш витратні методи. Так в статті пропонується застосовувати для таких цілей організаційні методи, а саме передачу деяких бізнес-процесів підприємства на аутсорсинг. Досліджено загальні відомості про аутсорсинг на підприємстві та запропоновано модель відбору бізнес-процесів підприємства для передачі їх на аутсорсинг.

In the article the actual problem of electrical industry enterprises to reduce production costs. Development of measures to r educe production costs for enterprises is an urgent problem for many businesses the electrical industry. Methodological and organizational bases of lower production costs of enterprises in the regulation of market economy has not sufficiently investigated. In times of economic hardship enterprises should be used to reduce their production costs Lowest cost method. Recently, one of the most promising areas of lower production costs in enterprises electrical equipment and instrumentation and have the opportunity to transfer to outsourcing expensive. When using outsourcing to domestic enterprises plan to achieve the following objectives: improve economic efficiency and reduce costs of economic activity; reducing the need for investment in the development of non-core activities; the creation of conditions to meet seasonal needs in additional staff; improving the quality of work performed and services transferred to outsourcing. Costs of business processes in detail might consider if automated systems that cover almost the entire life cycle of products and first used a process approach to management. Since the article proposed to use for purposes such organizational methods, namely the transfer of certain business processes outsourcing. To analyze the impact of changes in costs to the amount of profit a business process is proposed to use a model that presents linear dependence of profit on the cost of the implementation of business processes. Researched overview of outsourcing in the company and the model selection business processes to transfer them to outsource.
Reduction of electrical machines and apparatuses production costs by using business process outsourcing
Keywords: витрати; електротехнічна промисловість; зниження витрат; методи; аутсорсинг; бізнес-процеси; наскрізні бізнес-процеси; прибуток; критерії відбору; ефективність; costs; electrical industry; cost reduction; methods; outsourcing; business processes; through business processes; revenue; selection criteria; efficiency